The Effect of Using the Strategy of Roundhouse in the Achievement of Fourth Grade Students of Computer and Their Attitudes towards It (Journal Of Educational and Psychological Researches, 2022)
The research aims to identify the effect of using the strategy of Roundhouse on the achievement of fourth-grade students of computer and their Attitudes towards it. The research sample consisted of (61) fourth-grade secondary school students distributed into the experimental group consisted of (31) students study computer according to the Roundhouse strategy, and the control group consisted of (30) students follow the traditional method. The researcher designed an achievement test consisting of (30) items of multiple choice. To measure the attitudes of students towards the computer, a questionnaire of (32) paragraphs with three alternatives was designed by the researcher. The results showed that there is a statistically significant difference between the scores of the two research groups in the achievement test of the computer for the benefit of the experimental group. The results also showed a statistically significant difference between the scores of the two groups in the attitudes scale for the benefit of the experimental group.